(untitled) (International Journal of Physiotherapy, 2019)
Background: Posterior shoulder tightness has been proposed to contribute to or cause a myriad of shoulder conditions. The tightness of the posteroinferior capsule and the teres minor and infraspinatus muscles of the posterior cuff has been hypothesized to cause osteokinematic [e.g., limited glenohumeral (GH) internal rotation] and arthrokinematic dysfunctions (e.g., decentralization of the humeral head). A number of interventions have been successful in the restoration of or at least improvement in posterior shoulder flexibility including joint mobilizations (e.g., posterior glide) and posterior cuff stretches. The two most common posterior cuff stretches, the sleeper stretch and the crossbody stretch, mimic the position of two common impingement Orthopaedic provocation tests. Despite the success of stretching to help optimize tissue extensibility to help prevent injuries, these stretches have been reported to cause pain in some symptomatic subjects. For these reasons, the authors propose creating an alternate posterior shoulder self-stretching technique that facilitates the inhibition of the target region. Aim: Therefore, this paper aims to introduce a novel stretching protocol that utilizes a form of reflex inhibition to help relax the muscle during the stretching procedure to increase efficiency and reduce pain during the stretching maneuver. Underlying Principles for the Proposed Stretching Maneuver: This novel stretch is an active-assisted maneuver using a form of reciprocal inhibition. The authors propose that muscular inhibition through Ia afferents can be applied in a more global manner by muscle contraction of the anatomically remote posterolateral hip cuff musculature (gluteus maximus and medius) to inhibit the target muscles of the posterior rotator cuff of the scapulohumeral joint (infraspinatus and teres minor). This novel inhibitory stretching technique is referred to as Inhibition Stretching (IS), and the specific technique utilized in this study is the Clam Shell Bridging Maneuver. This technique is recommended for overhead athletes with and without shoulder pain and limited GH IR. Summary: The authors have proposed a novel stretching procedure, the Clam Shell Bridging Maneuver, that is hypothesized to reduce the muscles guarding, and resistance of the shoulder girdle during stretching and also position the athlete in a way that helps minimizes pain and impingement during the stretch while still providing stabilization to the scapula.